Novel anti-inflammatory effects of canagliflozin involving Hexokinase II in lipopolysaccharide-stimulated human coronary artery endothelial cells - Uthman, Laween; Kuschma, Marius Christian; Römer, Gregor; Boomsma, Marleen; Keßler, Jens; Hermanides, Jeroen; Hollmann, Markus W.; Preckel, Benedikt; Zuurbier, Coert J.; Weber, Nina C. (Cardiovascular drugs and therapy, 2021)
Vascular inflammation and disturbed metabolism are observed in heart failure and type 2 diabetes mellitus. Glycolytic enzyme hexokinase II (HKII) is upregulated by inflammation. We hypothesized that SGLT2 inhibitors Canagliflozin (Cana), Empagliflozin (Empa) or Dapagliflozin (Dapa) reduces inflammation via HKII in endothelial cells, and that HKII-dependent inflammation is determined by ERK1/2, NF-κB. and/or AMPK activity in lipopolysaccharide (LPS)-stimulated human coronary artery endothelial cells (HCAECs).
"Published online: 13 October 2020".- S. 1083
Gesehen am 23.09.2024